Model Kurikulum Program Studi Ekonomi Islam Masa Depan - Paturohman Paturohman (Ecopreneur : Journal of Sharia Economics Study Program, 2020)
This article describes the Islamic economic curriculum that has been designed by the Ministry of Religion to be applied in all Islamic tertiary institutions, both public and private, that open Sharia economic study programs. Following the development now that Islamic economics study programs are much in demand by prospective students to enter the study program. However, according to the author, the curriculum prepared by the Ministry of Religion still does not reflect the face of Islamic economics. Therefore, the authors conducted a research study in several universities in the three regions of Cirebon. The results turned out to be the author found five private Islamic tertiary institutions that opened Sharia economic study programs namely the Bunga Bangsa Islamic Institute of Cirebon, Cirebon Islamic Religious High School, Prince Dharma Khusuma Islamic High School, Segram Indramayu, ISI Fahmina, and Nahdhatul Ulama University Cirebon. While others such as IAIN Sheikh Nurjati and Ma'had Ali Babakan Cirebon College opened Sharia Economic Law study programs. Of the five Islamic universities that opened Sharia economic study programs that have seen more advanced developments, Sharia economic study programs at BBC IAI. And the author found the design of the Shariah economics curriculum for the future namely that Sharia economics courses reflect Islamic values ​​so that the output produces graduates of Shariah economists who are reliable and can ground the Islamic economy on the prosperous and richest Indonesia in the world. Keywords: curriculum; Islamic economics; Islamic tertiary institutions Abtrak Artikel ini memaparkan tentang kurukulum ekonomi Syariah yang telah didesain oleh Kementerian Agama untuk diterapkan di semua perguruan tinggi Islam baik negeri atau swasta yang membuka prodi ekonomi Syariah. Mengikuti perkembangan sekarang bahwa prodi ekonomi Syariah banyak diminati oleh calon-calon mahasiswa untuk masuk pada prodi tersebut. Akan tetapi kurikulum yang telah disiapkan oleh Kementerian Agama itu menurut penulis masih belum mencerminkan wajah ekonomi yang Islami. Oleh itu, penulis melakukan studi penelitian di beberapa perguruan tinggi di wilayah tiga Cirebon. Hasil penelitian ternyata penulis menemukan lima perguruan tinggi Islam swasta saja yang membuka prodi ekonomi Syariah yakni Institut Agama Islam Bunga Bangsa Cirebon, Sekolah Tinggi Agama Islam Cirebon, Sekolah Tinggi Agama Islam Pangeran Dharma Khusuma Segeran Indramayu, ISI Fahmina, dan Universitas Nahdhatul Ulama Cirebon. Sedangkan yang lain seperti IAIN Syekh Nurjati dan Sekolah Tinggi Ma’had Ali Babakan Cirebon membuka prodi Hukum Ekonomi Syariah, Dari kelima perguruan tinggi Islam yang membuka prodi ekonomi Syariah yang sudah terlihat nampak perkembangan lebih maju adalah prodi ekonomi Syariah di IAI BBC. Dan penulis menemukan desain kurukulum ekonomi Syariah untuk masa depan yakni bahwa mata kuliah-mata kuliah ekonomi Syariah mencerminkan nilai-nilai Islam sehingga output nya menghasilkan lulusan ekonom-ekonom Syariah yang handal dan bisa membumikan ekonomi Islam dibumi Indonesia yang makmur dan terkaya di dunia. Kata kunci: kurikulum; ekonomi Syariah; perguruan tinggi Islam